Instructing Low-Achievers in Mathematical Word Problem Solving - Kajamies A; Vauras M; Kinnunen R (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
We describe the effects of an intervention designed to develop the mathematical word problem solving of low-achievers. The eight students participating in the intervention were selected from 429 10-year-olds on the basis of their difficulties in word problem solving. In the intervention, we combined intensive, systematic, and explicit teacher scaffolding in the cognitive, metacognitive, and motivational activities involved in skillful problem solving with carefully designed word problems embedded in a computer-supported adventure game. The results from the pre-test, post-test, and follow-up test indicate significant effects for the intervention students' word problem solving compared to the two control groups. A single-subject study describes the results also at the individual level.